Ten-year, single center experience of ambulatory axillary intra-aortic balloon pump support for heart failure. Issue 5 (May 2022) - Nishida, Hidefumi; Ota, Takeyoshi; Onsager, David; Grinstein, Jonathan; Jeevanandam, Valluvan; Song, Tae
Highlights: In total, 241 patients underwent axillary intra-aortic balloon pump (IABP) support for heart failure. Ambulation was possible in 90.0% during axillary IABP support. Overall, 86.7% were successfully bridged to intended therapy. IABP-related stroke occurred in 2.5%. Abstract: Background: The axillary intra-aortic balloon pump has an advantage over the femoral intra-aortic balloon pump in terms of mobility. While axillary intra-aortic balloon pump has been widely used recently as a mode of mechanical circulatory support, the number of reported cases is limited. The purpose of this study is to summarize our experience and to evaluate the safety and efficacy of axillary intra-aortic balloon pump support. Methods: Between July 2009 and July 2019, 241 patients underwent axillary intra-aortic balloon pump support for heart failure. The intended therapeutic goals were bridge to heart transplantation (n=146), left ventricular assist device (n=66), and recovery (n=29). Intra-aortic balloon pumps were inserted through a graft sutured onto the axillary artery in 142 patients (58.9%) and percutaneously in 99 patients (41.1%). It was placed from the right axillary artery in 147 patients (61.0%) and left in 94 patients (39.0%). Primary outcome measures of interest included achievement of intended therapeutic goal, hemodynamic data, ambulatory data, intra-aortic balloon pump-related death, and complications. Results: Ambulation was possible in 217 patients (90.0%) during support. Hemodynamic parameters improved significantly after axillary intra-aortic balloon pump support. In total, 13 patients (5.4%) died and 10 patients (4.1%) required escalation of mechanical support. There were no deaths directly attributable to intra-aortic balloon pumps. Intra-aortic balloon pump-related stroke occurred in 6 patients (2.5%). Overall, 86.7% were successfully bridged to intended therapy (transplantation 90.4%, left ventricular assist device 90.9%, and recovery 58.6%). Conclusions: Axillary intra-aortic balloon pumps allow most patients to ambulate during support, improve hemodynamics, and lead to the intended goals successfully. Graphical abstract: Image, graphical abstract